Optimization of Biodiesel Production from Thevetia Peruviana Seed Oil using Transesterification Method - Ishaya, Zamani Donald; Samual, Joseph; Ede, Godwin Egbudu (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
Globally there is a rekindled interest to find alternative fuels to fossil fuel because of the issues of pollution and climate change associated with fossil fuels. Therefore, one of the alternatives is plant oil from non-edible sources. So, this study investigated the synthesis and optimization of biodiesel production from a novel non-edible feedstock (Thevetia Peruviana Seed Oil) using NaOH catalyst and methanol through transesterification route. The influence of parameters catalyst loading and alcohol-to-oil molar ratios on the yields of the biodiesel was checked. A mixture method of experimental design was adopted for the study. The results showed an optimal biodiesel yield of 98.87 % comprising of 80.02 % methyl esters and 18.85 % ethyl esters from the experiment with the reaction conditions; concentration of catalyst 0.25%, 9:1 methanol/oil molar ratio, 60 0C reaction temperature, 60 minutes reaction time and 150 rpm agitation speed. This study developed an optimal catalyst concentration, alcohol-to-oil molar ration, reaction temperature, reaction time and agitation speed for synthesizing biodiesel from Thevetia Peruviana Seed Oil and it also identifies the methyl esters %, ethyl esters % and free fatty acid (FFA) % present in the biodiesel. The study showed biodiesel can be produced from Thevetia Peruviana Seed Oil with a very high yield, this is a potential alternative to diesel fuel and can be applied to diesel engines to produce power for use in automobiles, farm machineries and electricity generation.